Structural Optimization and Electromagnetic Performance Research of Axial Magnetic Field Tidal Current Generators - Wenzhou Liu; Jinghuan Yang; Lixin Pei; Mohammad Rafiei; Yilong Yang; Yuliang Wang; Jiacheng Cui; Yun Guo; Baowen Zhang (Energies)
Tidal energy, as a stable and predictable renewable energy source, is garnering increasing attention. However, tidal energy generation faces challenges such as low energy conversion efficiency and high mechanical losses in low-velocity environments. To address these issues, this paper proposes a novel design for a tidal energy generator based on an axial field coreless structure. This design significantly reduces mechanical losses and enhances energy conversion efficiency by employing a direct-drive structure and a coreless stator. Additionally, the introduction of a Halbach array permanent magnet and soft magnetic composite further optimizes the generator’s electromagnetic performance, thereby increasing power output. Simulation results demonstrate that the designed generator can achieve a power output of 300 W at a tidal velocity of 1.8 m/s, with an average generation efficiency of 90.6%. This design exhibits excellent performance in low-velocity tidal environments and provides valuable technical support for the design of tidal energy generators.